Modul Asuhan Persalinan Kala III dengan Metode Preceptorship terhadap Keterampilan Mahasiswa DIII Kebidanan - Yatri Hilinti; Prastawa Budi; Mardiana Ahmad (Jurnal Keperawatan Silampari, 2020)
This study aims to analyze the effect of the third stage of childbirth care modules with the preceptorship method on the skills of midwifery DIII students. Quasyeksperiment research design. The results showed that the modules and preceptorship methods were better in improving the skills of students doing third stage of childbirth care. Conclusion, there was an increase in student skills in all groups namely the demonstration group, modules and demonstrations as well as the modules and preceptorship, the highest increase in the skills of third stage of childbirth care was obtained by the group given the third stage of childbirth care modules and the preceptorship method compared to the demonstration group and the modules and demonstration groups without the intervention of the third stage of childbirth care modules Keywords: Stage III, Skills, Modules, Delivery, Preceptorship